2014
DOI: 10.1073/pnas.1404109111
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic neuronal stimulation promotes functional recovery after stroke

Abstract: Clinical and research efforts have focused on promoting functional recovery after stroke. Brain stimulation strategies are particularly promising because they allow direct manipulation of the target area's excitability. However, elucidating the cell type and mechanisms mediating recovery has been difficult because existing stimulation techniques nonspecifically target all cell types near the stimulated site. To circumvent these barriers, we used optogenetics to selectively activate neurons that express channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
206
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(218 citation statements)
references
References 50 publications
11
206
1
Order By: Relevance
“…For Parkinson's disease [191,192], the goal has been to modulate the basal ganglia circuits in a way that is achieved with deep brain stimulation but with better spatial and temporal control. For stroke [193], excitatory optogenetics has been used to strengthen the function of intact circuits so that they can restore lost motor function. After spinal cord injury [194,195], optical control of spinal neurons distal to the lesion could establish control of circuits that have been disconnected from brain control.…”
Section: Resultsmentioning
confidence: 99%
“…For Parkinson's disease [191,192], the goal has been to modulate the basal ganglia circuits in a way that is achieved with deep brain stimulation but with better spatial and temporal control. For stroke [193], excitatory optogenetics has been used to strengthen the function of intact circuits so that they can restore lost motor function. After spinal cord injury [194,195], optical control of spinal neurons distal to the lesion could establish control of circuits that have been disconnected from brain control.…”
Section: Resultsmentioning
confidence: 99%
“…In stroke patients with good recovery, there is often a transient bilateral activation that occurs in both cortical hemispheres while moving the affected limb, suggesting the involvement of contralesional cortical activation in stroke recovery [23][24][25]. Data from our laboratory and that of others have shown that increasing the excitability of the ipsilesional motor cortex (iM1) after stroke is beneficial for recovery [5,23,26,27]. However, it is less clear whether activation of other areas such as the contralesional cortex is beneficial or maladaptive, or not involved [28].…”
Section: Functional Recovery After Strokementioning
confidence: 93%
“…This cell type specificity allows manipulation of specific circuits and thus more targeted manipulations, which should help pinpoint the circuits and molecular mechanisms that underlie diseases. Optogenetic approaches have been used in rodents to probe neural circuits for several neurological/neurodegenerative diseases, including Parkinson's disease [78,79], epilepsy [80,81], and stroke [26,82]. In the next sections we will first introduce optogenetics and its developments, and then review the current understanding of remapping and recovery after stroke from recent studies using peripheral and optogenetic stimulation, as well as the use of optogenetic stimulation to enhance post-stroke recovery.…”
Section: Current Brain Stimulation Techniques Used To Study Stroke Rementioning
confidence: 99%
See 2 more Smart Citations